HEMORHEOLOGICAL PROFILE AND LIPID SPECTRUM IN PATIENTS IN THE ACUTE PHASE OF ISCHEMIC STROKE - V. V. Yakusevich; S. V. Lychenko; A. Yu. Malygin (Klinicist)
Objective: to assess the specific features of the hemorheological profile and lipid spectrum in patients in the acute phase of ischemic stroke inthe presence of arterial hypertension (AH). Subjects and methods. Fifty patients divided into 2 groups were examined. Group 1 included 30 patients (mean age 67 .0± 10.1 years) with acute ischemic stroke. They all were diagnosed as having grade 2 AH as evidenced by medical records. Group 2 comprised 20 apparentlyhealthy individuals (50 ± 48 years) without AH. The parameters of the hemorheological profile and lipid spectrum were determined in allthe enrolled patients.Results. Among the blood macrorheological characteristics, there was a rise in plasma viscosity in the study group, which was 17 % greaterthan in group 2 (2.10 ± 0.25 and 1.80 ± 0.23 mPas, respectively; p < 0.01). The most important results were obtained in the study of bloodmicrorheological characteristics. All the study parameters were considerably higher in the patients with acute ischemic stroke than those in the apparently healthy individuals. Thus, the formation rate for aggregates (0.50 ± 0.24 and 0.32 ± 0.20 relative units in Groups 1 and 2, respectively; p < 0.01) and their sizes (7.30 ± 1.02 and 6.20 ± 0.63 relative units, respectively; p < 0.01) were more in the study group thanthose in the control one. At the same time, in the study group the integral aggregation index was 80 % higher (p < 0.01) than that in the control. However, in the patients with acute ischemic stroke, the erythrocyte rigidity index was lower than that in apparently healthy patients (0.71 ± 0.07 and 0.76 ± 0.09 relative units, respectively; p < 0.05). In Group 1 patients, impairments of the hemorheological profile were accompanied by changes in the lipid spectrum. Despite the fact that no differences in total cholesterol levels were recorded in the study groups (4.7 ± 1.5 and 5.20 ± 1.02 mmole/l in Groups 1 and 2, respectively), there was a substantial change in the other parameters of the lipid spectrum. Thus, in the patients with acute ischemic stroke, the levels of high-density lipoprotein cholesterol were 62 % lower than in the control group (p < 0.01) and the atherogenicity coefficient was 1.5-fold higher in the study group than in the control one (p < 0.01). At the same time, there were increases in triglycerides in Groups 1 and 2 (1.33 ± 0.74 and 0.96 ± 0.55 mmol/l, respectively; p < 0.05) and low-density lipoprotein cholesterol in these groups (3.10 ± 0.78 and 1.96 ± 0.60 mmol/l, respectively; p < 0.01).Conclusion. The changes in the lipid spectrum and hemorheological profile can provide a more detailed insight into the pathogenic processesoccurring in the patients in the acute phase of ischemic stroke.